PENGKINIAN MANUAL KAPASITAS JALAN INDONESIA 1997 - Erwin Kusnandar (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
Indonesian Highway Capacity Manual (IHCM), 1997, as a manual for the analysis, design planning and operations ofroad traffic facilities is a research product that was conducted empirically by considering various traffic characteristics representing traffic condisions in Indonesian area, the resulted value of analysis parameters is not absolute, but changeable depending on time and locations. Since it was published, transportation infrastructure and road user conditions experience lots of changes in terms of both quantity and quality, resulting in outdated analysis parameters of traffic and road infrastructure conditions.Those outdated analysis parameters can cause over-designs or under- designs in road technical design products. A series of actions and corrections has to be formulated on IHCM 1997 by identifying parameter problems as one of the factors that forms the traffic charactristics and road performance including analysing the present regulations. In general, the problems tend to lead to the necessity of updating the manual by conducting a consensus to stadardize it in user- friendly formatted. Key word : IHCM renewal, road traffic performance, road environment, traffic volume, traffic growth